Identification of a new HLA-A*0201-restricted T-cell epitope from the tyrosinase-related protein 2 (TRP2) melanoma antigen - Sun, Yuansheng; Song, Mingxia; Paschen, Annette; Schadendorf, Dirk (International journal of cancer, 2000)
For the development of peptide-based immunotherapies, the identification of additional tumor antigens and T-cell epitopes is required. Because HLA-A*0201 is the most common allele in Caucasians, who represent the majority of patients with melanomas, 6 peptides carrying an HLA-A*0201 motif were synthesized from tyrosinase-related protein-2 (TRP2) melanoma antigen and tested for binding affinity to the HLA allele using processing-defective T2 cells. These peptides were then pulsed onto autologous dendritic cells and used to stimulate in vitro CD8+-enriched T cells isolated from peripheral blood of HLA-A*02+ healthy donors or melanoma patients for the induction of specific cytotoxic T lymphocytes (CTLs). One peptide, TRP2288-296 (SLDDYNHLV), the best HLA-A*0201 binder, elicited specific CTLs from 1 of 4 patients and 3 of 4 healthy donors. The induced CTLs from the patient and from 1 donor efficiently recognized HLA-A*02+ TRP2+ melanomas as well as COS-7 cells expressing HLA-A*0201 and TRP2 in an HLA class I-restricted manner, as assessed by cytokine production and direct cytolysis. The remaining 2 CTL lines derived from 2 donors displayed low T-cell receptor avidity, which could lyse melanoma cells in the presence of exogenous peptide. Since TRP2 is an antigen expressed in most melanomas, identification of the TRP2/HLA-A*0201 peptide SLDDYNHLV may facilitate the design of present peptide-based immunotherapies for the treatment of a large fraction of melanoma patients.
Gesehen am 25.02.2019